Clinical performance and survivorship of navigated floating platform mobile‐bearing total knee arthroplasty: A minimum 10‐year follow‐up. Issue 3 (19th May 2017) - Kim, Sang‐Min; Seo, Jai‐Gon; Lim, Seung‐Jae; Lim, Hyung‐Tae; Cho, Chang‐Ho; Moon, Young‐Wan
Abstract: Background: The purpose of this study is to report the outcome of navigation‐assisted cruciate‐retaining total knee arthroplasty (TKA) using one type of cemented, second‐generation, floating‐platform (FP), mobile‐bearing system. Methods: Forty‐two patients who underwent cruciate retaining TKAs using e.motion‐FP prostheses under navigational guidance were retrospectively reviewed. The preoperative diagnosis was osteoarthritis in all knees except one rheumatoid arthritis. The mean follow‐up was 132.0 months (range, 120–140 months) and the mean age was 64.0 ± 4.7 years (range, 51–76 years) at the time of index surgery. Clinical and radiographic results as well as mechanical survival rate of this type of prosthesis were investigated at a minimum follow‐up of 10 years. Results: The mean mechanical femorotibial angle was improved from 11.7° ± 3.3° preoperatively to 1.4° ± 1.7° at the latest follow‐up. No prosthesis‐related complications occurred. One knee underwent open debridement due to superficial infection at 5 weeks after surgery and the other knee experienced a periprosthetic fracture around the proximal tibia, which was successfully healed after open reduction and internal fixation. Conclusions: The e.motion‐floating platform mobile‐bearing design yielded satisfactory long‐term durability and implant performance under navigational guidance.